2008
DOI: 10.1002/eat.20601
|View full text |Cite
|
Sign up to set email alerts
|

The rising prevalence of comorbid obesity and eating disorder behaviors from 1995 to 2005

Abstract: Comorbid obesity and ED behaviors are an increasing problem in our society. Prevention and treatments efforts for obesity and EDs must consider and address this increasing comorbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
73
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 118 publications
(84 citation statements)
references
References 20 publications
4
73
0
3
Order By: Relevance
“…The main findings of the present study are as follows: The prevalence of overweight bulimic patients in our sample is notably higher compared with a previous study performed in 1990 [5], and our findings seem to confirm the increased risk of developing BN in overweight and obese subjects observed in the last two decades [12,13]. A recent community study reported that two-thirds of bulimic patients were overweight/obese [14].…”
Section: Discussionsupporting
confidence: 86%
“…The main findings of the present study are as follows: The prevalence of overweight bulimic patients in our sample is notably higher compared with a previous study performed in 1990 [5], and our findings seem to confirm the increased risk of developing BN in overweight and obese subjects observed in the last two decades [12,13]. A recent community study reported that two-thirds of bulimic patients were overweight/obese [14].…”
Section: Discussionsupporting
confidence: 86%
“…These findings seem to point to the importance of binge ED as an autonomous ED, in need of appropriate public health attention. Binge ED has a role in the development of obesity (Yanovski, 2003): indeed, recent consecutive population surveys found that increasing prevalence of binge eating behaviours was associated to a faster increasing comorbidity with obesity (Darby et al, 2009). …”
Section: Any Binge Eatingmentioning
confidence: 99%
“…In addition to high rates of medical morbidity, obesity commonly co-occurs with eating disorders (Neumark-Sztainer, 2009), with recent research indicating the lifetime prevalence of obesity is over 80% among individuals with binge eating disorder (Villarejo et al, 2012). Yet, a substantial number of overweight and obese persons engage in disordered eating behaviors that do not meet criteria for a diagnosable eating disorder (ED) (Hay, Mond, Buttner, & Darby, 2008;Mond, Hay, Rodgers, & Owen, 2009), and some studies suggest that the co-occurrence of obesity and disordered eating behaviors has increased (Darby et al, 2009). Binge eating is present among 23-46% of overweight or obese persons (Bulik, Sullivan, & Kendler, 2002), and other research has theorized that dietary restraint (Polivy & Herman, 1985) (i.e., cognitive [mental] efforts to reduce or limit what one is eating, independently of whether or not such efforts are successful) may represent a risk factor for development of overweight and obesity if an individual experiences lapses in their cognitive control over eating (Fairburn & Harrison, 2003;Polivy & Herman, 1985;Stice, 2002).…”
Section: Introductionmentioning
confidence: 99%